1992
DOI: 10.2307/1938730
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Ecology of an Insect Host‐Parasitoid Association: The Pea Aphid‐Aphidius Ervi System

Abstract: Evolutionary host—size models assume that host quality for parasitoid growth and development is a linear function of host size. To test this assumption, we compared the growth patterns of the hymenopteran parasitoid Aphidius ervi when it developed in different nymphal instars of apterous pea aphids, Acyrthosiphon pisum. At daily intervals, unparasitized aphids and aphids that were parasitized at age 24, 48, 72, and 120 h (corresponding to nymphal instars L1—L4) were dissected. We weighed parasitoid larvae and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
161
2
12

Year Published

1995
1995
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(184 citation statements)
references
References 37 publications
9
161
2
12
Order By: Relevance
“…Larval stage and longevity of parasitoids (Vinson & Iwantsch 1980), allowing host quality to be directly evaluated, since the shortest development period can be considered as the best growth trajectory (Sequeira & Mackauer 1992). In recent studies, many authors have observed durations of the development period of A. colemani higher than 12.2 days, different from those observed in this work for that developmental stage (Gonçalves-Gervásio et al 2001).…”
Section: Treatmentsmentioning
confidence: 58%
“…Larval stage and longevity of parasitoids (Vinson & Iwantsch 1980), allowing host quality to be directly evaluated, since the shortest development period can be considered as the best growth trajectory (Sequeira & Mackauer 1992). In recent studies, many authors have observed durations of the development period of A. colemani higher than 12.2 days, different from those observed in this work for that developmental stage (Gonçalves-Gervásio et al 2001).…”
Section: Treatmentsmentioning
confidence: 58%
“…Aphids are attacked by several groups of primary parasitoids, all solitary koinobiont endoparasitoids [19]. Parasitoids typically attack pre-adult aphids but their larvae do not destructively consume the host until late in development [20,21]. The fullgrown parasitoid larva pupates inside the mummified husk of its host.…”
Section: Introductionmentioning
confidence: 99%
“…Patterns of preference are not fixed, however, but often vary with the availability and relative abundance of different host types (Chow & Mackauer, 1991) and the female's physiological state, including her egg load, previous reproductive success, and age (Weisser, 1994;Michaud & Mackauer, 1995;Mackauer et al, 1996). Older instars and adult aphids are larger than first and second instars and, potentially, con tain more nutritional resources; however, these resources may not always be accessible by the parasitoid (Sequeira & Mackauer, 1992). Moreover, large aphids can better defend themselves against attacks and therefore may be more costly to the female than small aphids (Gerling et al, 1990;Chau & Mackauer, 1997;Losey & Denno, 1998).…”
Section: Introductionmentioning
confidence: 99%